2016
DOI: 10.1002/jcph.846
|View full text |Cite
|
Sign up to set email alerts
|

Model‐Based Dose Selection for Intravaginal Ring Formulations Releasing Anastrozole and Levonorgestrel Intended for the Treatment of Endometriosis Symptoms

Abstract: Pharmacokinetics (PK) of anastrozole (ATZ) and levonorgestrel (LNG) released from an intravaginal ring (IVR) intended to treat endometriosis symptoms were characterized, and the exposure-response relationship focusing on the development of large ovarian follicle-like structures was investigated by modeling and simulation to support dose selection for further studies. A population PK analysis and simulations were performed for ATZ and LNG based on clinical phase 1 study data from 66 healthy women. A PK/PD model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 39 publications
2
35
0
1
Order By: Relevance
“…As a result, these doses were selected for the phase 2 dose-finding study. 8 It should be noted that for these simulations it was anticipated that there would be no effect of ATZ on LNG. However, potential DDIs have not been clinically investigated to date, as an IVR administering only LNG was not included in the phase 1 program.…”
mentioning
confidence: 99%
“…As a result, these doses were selected for the phase 2 dose-finding study. 8 It should be noted that for these simulations it was anticipated that there would be no effect of ATZ on LNG. However, potential DDIs have not been clinically investigated to date, as an IVR administering only LNG was not included in the phase 1 program.…”
mentioning
confidence: 99%
“…Intravaginal ring which consists of Anastrozole and Levonogestrel has been brought into experimental practice and it was proposed that constant drug plasma levels can be achieved due to the continuous release of drug from the intravaginal ring. The efficacy of intravaginal drug delivery was uncertain but it was shown that by avoiding the first-pass metabolism in the liver, equivalent efficacy could be accomplished and unwanted side effects were reduced [31,32]. In a study done on cynomolgus monkeys using the vaginal rings, the circulating estrogen level was found to be reduced by at least 30% without leading to ovarian hyperstimulation caused by the pituitary counter regulatory pathway [33].…”
Section: Pain In Endometriosismentioning
confidence: 99%
“…In addition, the results show that ATZ is appropriate for a polymer vaginal drug delivery system and absorbed into blood by vaginal mucosa. ATZ IVRs can also be applied in the treatment of EM (Reinecke, Schultze‐Mosgau, Nave, Schmitz, & Ploeger, ). The drug located near the treatment site improved the partial drug concentration in blood and the treatment effect is more apparent with fewer side effects.…”
Section: Introductionmentioning
confidence: 99%